Efeito do tempo e da temperatura sobre a viabilidade de tecido ovariano de fetos bovinos - Melo Júnior, Jairo de (2017)
The aim of this study was to establish the best time interval and the ideal temperature of the medium to carry the ovaries from bovine fetuses from the collection site to the laboratory. The morphology and integrity of the preantral follicles and tissue viability were the evaluated parameters. For this, the work was divided into two steps. In the first one, (Experiment 1), ovaries of bovine fetuses, were transported in thermal bottles with temperatures of 4 ° C, 22 ° C and 33 ° C. In the Experiment 2 was carried out, tested for viability by the time it took to be manipulated, and each group was manipulated with intrevals of 4hs, 10hs and 16hs after their collection. Experiment 1 demonstrated that the highest proportion (P <0.05) of viable preantral follicles was observed at 4°C. The group of 33°C showed the highest tissue degeneration emitted bypropidium iodide. The proportion of primordial follicles was lower (P <0.05) in all treatment groups after in vitro culture compared to control and D0. Experiment 2 demonstrated that the viability and morphology of the follicles was better during the 4 hour time interval compared to the 10 and 16 hour intervals. The group transported for 4 hours presented the lower fluorescence emission relative to apoptotic cell index (P <0.05) to the control and to the other treatment groups. The results showed that the best temperature for the transport of ovaries of bovine fetuses is 4 °C and the best interval for this to be done is 4 hours.